A Literature Review on the Effectiveness of Problem-Based Learning in Enhancing Biology Students’ Problem Solving Skills and Learning Outcomes - Risalatul Muawanah; Ananda Fitri Ar Ridho; Nuril Badriyah; Fatimatus Zahro; Yamin Yamin (Equator Science Journal, 2025)
This study aims to review the effectiveness of the Problem-Based Learning (PBL) learning model in improving students' problem-solving skills and learning outcomes in Biology. This study was conducted using a literature review method of relevant national and international articles. Data sources were obtained through a Google Scholar search with the keywords "Problem-Based Learning" and "Biology", and were selected based on the criteria of the year of publication (2018–2024), relevance to the field of science, and presentation of quantitative data. The analysis techniques used include descriptive analysis, content analysis, and critical analysis. The results of the study show that the PBL model consistently improves students' learning outcomes and critical thinking skills compared to conventional methods. The increase in students' average scores was recorded between 4% and 24%, depending on the combination of approaches, such as audio-visual-based PBL, concept mapping, scaffolding, and role playing. In addition to cognitive aspects, PBL has also been shown to strengthen students' social skills, including cooperation, communication, and self-confidence in group discussions. The success of implementing this model is highly dependent on the role of the teacher as a facilitator, students' readiness for independent learning, and the support of interactive media. Therefore, PBL is recommended to be applied in Biology learning as an approach that can improve students' academic achievements as well as 21st century competencies.